Fluorescence quenching in oligonucleotides containing 7-substituted 7-deazaguanine bases prepared by the nicking enzyme amplification reaction - Ménová, Petra; Dziuba, Dmytro; Güixens-Gallardo, Pedro; Jurkiewicz, Piotr; Hof, Martin; Hocek, Michal (Bioconjugate chemistry, 2015)
Recently, we reported the use of the Nicking Enzyme Amplification Reaction (NEAR) for the enzymatic synthesis of short oligonucleotides (ONs) containing 5-substituted pyrimidine or 7-substituted 7-deazaadenine nucleotides. Since no oligonucleotide products were visible on agarose gels stained by an intercalating dye (GelRed), we assumed that the method did not work for 7-substituted 7-deazaguanine deoxyribonucleoside triphosphates. We revisited the work and found that the NEAR method works for 7-deazaguanine nucleotides as well but that the resulting modified ONs quench the fluorescence of DNA intercalators, rendering them invisible on gel electrophoresis stained by them. Here, we report on the modified methodology for the NEAR synthesis and analysis of G-modified ONs and on quantification of the fluorescence quenching.
Keywords: fluorescence; guanin; Guanine; Base Sequence; Fluorescence; Fluorescent Dyes; Oligonucleotides; Spectrometry, Fluorescence; oligonukleotidy; fluorescenční barviva; sekvence nukleotidů; fluorescenční spektrometrie